Quantification of T-Cell and B-Cell Replication History in Aging, Immunodeficiency, and Newborn Screening - Verstegen, Ruud H. J.; Aui, Pei M.; Watson, Eliza; De Jong, Samuel; Bartol, Sophinus J. W.; Bosco, Julian J.; Cameron, Paul U.; Stirling, Robert G.; de Vries, Esther; van Dongen, Jacques J. M.; van Zelm, Menno C. (Frontiers in Immunology, 2019)
Quantification of T-cell receptor excision circles (TRECs) has impacted on human T-cell research, but interpretations on T-cell replication have been limited due to the lack of a genomic coding joint. We here overcome this limitation with multiplex TRG rearrangement quantification (detecting 0.98 alleles per TCRαβ+ T cell) and the HSB-2 cell line with a retrovirally introduced TREC construct. We uncovered <5 cell divisions in naive and >10 cell divisions in effector memory T-cell subsets. Furthermore, we show that TREC dilution with age in healthy adults results mainly from increased T cell replication history. This proliferation was significantly increased in patients with predominantly antibody deficiency. Finally, Guthrie cards of neonates with Down syndrome have fewer T and B cells than controls, with similar T-cell and slightly higher B-cell replication. Thus, combined analysis of TRG coding joints and TREC signal joints can be utilized to quantify in vivo T-cell replication, and has direct applications for research into aging, immunodeficiency, and newborn screening.